Perlindungan Hukum Direksi BUMN dalam Perspektif Business Judgment Rule dan Good Corporate Governance Pasca KUHP Baru - Wirawan B. Ilyas; Ramlani Lina Sinaulan (JOM, 2026)
The purpose of this study is to discover the mechanism for strengthening the protection for the Directors of Indonesian State-owned Enterprises through the Business Judgment Rule and the implementation of Good Corporate Governance so that business policies that have been implemented are not interfered with by law enforcers, for the company's going concerns.  A normative judicial research method was conducted with primary source materials, including laws related to BUMN and Limited Liability Companies which serve as the reference for the implementation of the company's goals and objectives for the benefit of society based on professionalism. Secondary materials were also used in the form of textbook publications, journals in the field of corporate governance, and court decisions related to the issues. The study concludes that the Principles of Business Judgment Rule and Good Corporate Governance guidelines are important references that can protect the directors in running the company. Secondly, the meaning of 'State Financial Loss' is not only understood in the context of the provisions of the criminal act of corruption if there is a loss from a transaction carried out by a company. The meaning of loss in a company must also be viewed from an accounting perspective which has a different meaning from the legal perspectives that are universally subject to financial accounting standards.